Glycolysis and the Pentose Phosphate Pathway Promote LPS-Induced NOX2 Oxidase- and IFN-β-Dependent Inflammation in Macrophages - Jonathan R. Erlich; Eunice E. To; Raymond Luong; Felicia Liong; Stella Liong; Osezua Oseghale; Mark A. Miles; Steven Bozinovski; Robert D. Brooks; Ross Vlahos; Stanley Chan; John J. O'Leary; et al. (MDPI AG, 2022)
Macrophages undergo a metabolic switch from oxidative phosphorylation to glycolysis when exposed to gram-negative bacterial lipopolysaccharide (LPS), which modulates antibacterial host defence mechanisms. Here, we show that LPS treatment of macrophages increased the classical oxidative burst response via the NADPH oxidase (NOX) 2 enzyme, which was blocked by 2-deoxyglucose (2-DG) inhibition of glycolysis. The inhibition of the pentose phosphate pathway with 6-aminonicotinamide (6-AN) also suppressed the LPS-induced increase in NOX2 activity and was associated with a significant reduction in the mRNA expression of NOX2 and its organizer protein p47phox. Notably, the LPS-dependent enhancement in NOX2 oxidase activity was independent of both succinate and mitochondrial reactive oxygen species (ROS) production. LPS also increased type I IFN-β expression, which was suppressed by 2-DG and 6-AN and, therefore, is dependent on glycolysis and the pentose phosphate pathway. The type I IFN-β response to LPS was also inhibited by apocynin pre-treatment, suggesting that NOX2-derived ROS promotes the TLR4-induced response to LPS. Moreover, recombinant IFN-β increased NOX2 oxidase-dependent ROS production, as well as NOX2 and p47phox expression. Our findings identify a previously undescribed molecular mechanism where both glycolysis and the pentose phosphate pathway are required to promote LPS-induced inflammation in macrophages.